Varsity team sport coaches' perceptions of their roles and responsibilities. - Miller, Patricia S. (University of Ottawa (Canada), 1996)
The purpose of this study was to describe the perceptions of varsity team sport coaches roles and responsibilities within the university setting. In-depth interviews were conducted with eight full-time varsity basketball and volleyball coaches from four universities in Ontario, and inductively analyzed following procedures similar to Cote, Salmela and Russell (1995a). Three major categories emerged from the analysis including the athletic, educational and professional roles. The athletic role described the activities of the coaches concerning the athletic performance of their athletes and organization of their varsity programs. Within the organizational property of this category, planning competition and administrative tasks emerged as important coaching responsibilities. The educational role included the reported activities of the coaches regarding academic pursuits and personal development of their student athletes. The coaches assumed active roles in the academic lives of their athletes and facilitated the educational process by placing academics as a priority. The personal development property represented the roles of the coaches as counselors and parental figures, and teachers of life skills and priorities. The professional role described the obligations of the coaches towards the development of their sport and the coaching profession, as well as the conditions of working within an educational setting at the university level. While consistent with earlier research on the role of coaches in the skill development, academic achievement and the development of life skills, the results illustrated an athlete-centered approach associated with coaching within an educational setting. The findings provided new directions for future research.
Keywords: Education, Physical.